An Innovative Superconducting Magnetic Trap for Probing β-decay in Plasmas - Mauro, Giorgio Sebastiano; Celona, Luigi; Torrisi, Giuseppe; Pidatella, Angelo; Naselli, Eugenia; Russo, Filippo; Mazzaglia, Maria; Galatà, Alessio; Maimone, Fabio; Lang, Ralf; Tinscher, Klaus; Santonocito, Domenico; et al. (Frontiers in Physics, 2022)
The main aim of Plasmas for Astrophysics Nuclear Decays Observation and Radiation for Archaeometry (PANDORA) project is to build a compact and flexible magnetic plasma trap where plasma reaches a density n_e 10^11 - 10^13 cm^-3, and a temperature, in units of kT, kT_e 0.1 - 30 keV in order to measure, for the first time, nuclear β-decay rates in stellar-like conditions. One of the most important aspects of an ECR Ion Source (ECRIS) is its magnetic system. In this paper, the numerical design of the PANDORA magnetic system is presented and validated by using the commercial simulators OPERA and CST Studio Suite, showing an excellent agreement between each other in terms of axial and radial field profiles. In conjunction to the magnetic system design, the overall injection system, including the microwave lines for plasma heating and the isotopes injection schemes with a focus on the developments of the oven for solid elements, has been conceived and will be discussed.